Economy and Healthcare: Their Role in Providing Medical Care and Maintaining Public Health - OSADCHUK, Michail A.; OSADCHUK, Alexey M.; KORZHENKOV, Nikolay P.; TRUSHIN, Maxim V. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
Healthcare is the most important economy sector, which is designed to ensure preservation and strengthening of each person`s physical and mental health, maintaining his long-term active life by providing highly qualified medical and preventive care.Although human health does not have an accurate market price, it has the highest value for society and the individual. This indirectly allows us to consider it as an economic category. All health systems, depending on the prevailing source of funding, are divided into: social insurance (Germany, France, Japan, Russia), state (UK) and market (USA) ones. Studying international health systems, using new digital medicine developments, artificial intelligence elements and scientific analysis in medical practice opens up broad prospects for the sound management of economic resources.